Trade Diversion and Labor Market Outcomes - Natalie Chen; Dennis Novy; Diego Solórzano (CESifo GmbH, 2025)
In 2018 and 2019, the US administration increased tariffs on imports from China. Did these tariffs lead to more US imports from other countries such as Mexico? Using highly disaggregated data on the universe of Mexican firm-level exports, we find evidence of trade diversion from China to Mexico. We then combine the export data with detailed longitudinal employer-employee data to investigate the impact of trade diversion on labor market outcomes for workers employed by Mexican exporters. We find that trade diversion increased the labor demand of exporters exposed to US tariffs against China, resulting in more employment and higher wages, especially for low-wage workers such as female, unskilled, younger, and non-permanently insured employees. The effects were concentrated in technology and skill-intensive manufacturing industries.
Keywords: F12; F14; L11; 330; employment; exports; firms; tariffs; trade costs; trade diversion; wages; workers